Order picking performance improvement through storage location assignment: the case of a hardware wholesaler - Liu, Zelin; Rapp, Chad; Buquid, Jude; Aktas, Emel (Cranfield University, 2022)
Order picking is the most time-consuming, labour-intensive, and costly activity in picker-to-parts picking systems. The literature frequently minimises picking time but ignores the picking error, which affects picking efficiency and customer satisfaction. This paper to minimise picking time and picking error using multi-objective optimisation. Three storage location assignment policies, i.e., ABC-based, product-popularity-based (PPB) and product-relation-based (PRB), are deployed to minimise the picking time. PPB policy gave both the minimum picking time and picking error, with the trade-off between the two objectives presented in a Pareto frontier. Hence, the managers can determine a storage policy based on the optimisation results.
Keywords: Multi-objective optimisation; Picking time and error; Warehouse operations